2007
DOI: 10.1038/nm1585
|View full text |Cite
|
Sign up to set email alerts
|

TH17 cells contribute to uveitis and scleritis and are expanded by IL-2 and inhibited by IL-27/STAT1

Abstract: T-helper type 17 cells (T(H)17) are implicated in rodent models of immune-mediated diseases. Here we report their involvement in human uveitis and scleritis, and validate our findings in experimental autoimmune uveoretinitis (EAU), a model of uveitis. T(H)17 cells were present in human peripheral blood mononuclear cells (PBMC), and were expanded by interleukin (IL)-2 and inhibited by interferon (IFN)-gamma. Their numbers increased during active uveitis and scleritis and decreased following treatment. IL-17 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
691
2
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 748 publications
(742 citation statements)
references
References 44 publications
39
691
2
10
Order By: Relevance
“…In addition to PGE 2 , inflammation mediators can induce the release of other inflammatory cytokines such as IL‐6. Several previous studies demonstrated that IL‐6 plays an important role in ocular inflammation 31, 32, 33, 34. In this study, we found that production of IL‐6 increased 4.6 and 6.3 times in tears and aqueous humor, respectively, after ocular inflammation was induced.…”
Section: Resultssupporting
confidence: 63%
“…In addition to PGE 2 , inflammation mediators can induce the release of other inflammatory cytokines such as IL‐6. Several previous studies demonstrated that IL‐6 plays an important role in ocular inflammation 31, 32, 33, 34. In this study, we found that production of IL‐6 increased 4.6 and 6.3 times in tears and aqueous humor, respectively, after ocular inflammation was induced.…”
Section: Resultssupporting
confidence: 63%
“…Recently, a new insight with Th17 cells has emerged for the pathogenesis of EAU (Amadi-Obi et al 2007). In the present study, OPN-siRNA treatment suppressed not only Th1 cytokines but also IL-17 production, which could also account for the amelioration of EAU.…”
Section: Discussionmentioning
confidence: 99%
“…EAU induced with immunization of retinal Ag now represents not only Th1 but also Th17-cell-mediated ocular diseases. A massive inflammatory infiltration composed primarily of mononuclear cells causes a rapid and irreversible destruction of photoreceptor cells (Jiang et al 1999;Silver et al 1999;Caspi 2003;Amadi-Obi et al 2007;Luger et al 2008). It has been demonstrated that the augmentation of the Th2 response and T regulatory cytokine production and down-regulation of the Th1 response can mitigate inflammation and protect against the development of EAU (Saoudi et al 1993;Kezuka et al 1996;Caspi 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although these studies suggest the possible involvement of Th17 cells in clinical uveitis, more direct and compelling evidence has come from studies in experimental autoimmune uveitis (EAU) [13]. In this well-characterized mouse model of human uveitis [14], dynamic changes in the levels of IL-17-expressing cells occur during the course of uveitis [15]. Before the inception of EAU, only trace numbers of IL-17-expressing T cells are detectable in the PBMCs, LNs or retina but their numbers in these tissues increase with disease progression, with the highest levels detected in the retina at the peak of disease [15].…”
Section: Introductionmentioning
confidence: 99%
“…In this well-characterized mouse model of human uveitis [14], dynamic changes in the levels of IL-17-expressing cells occur during the course of uveitis [15]. Before the inception of EAU, only trace numbers of IL-17-expressing T cells are detectable in the PBMCs, LNs or retina but their numbers in these tissues increase with disease progression, with the highest levels detected in the retina at the peak of disease [15]. On the other hand, recovery from the disease coincides with rapid diminution in the IL-17-expressing T cells [15].…”
Section: Introductionmentioning
confidence: 99%